The Importance of Handwashing with Soap for the Health and National Defense Values of Students at Panunggangan 4 Elementary School - Richie Ricardo; Kevin Pranata; Jerry Alexander Jenmartin; Ferdy Anthonius; Christian Siregar (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2026)
This study aims to determine the level of knowledge, awareness, and habits of elementary school students regarding Handwashing with Soap (CTPS) behavior at SDN 4 Panunggangan. CTPS is an important part of clean and healthy living behavior that plays a role in preventing the spread of disease, especially in early childhood. The research method used a qualitative approach through the distribution of questionnaires to 25 first-grade students and structured interviews with two teachers. The results showed that some students had understood the importance of maintaining hand hygiene and washing hands after using the toilet. However, students' understanding of the appropriate time to wash their hands, especially after playing outdoors, and knowledge of the correct handwashing steps are still low. Teacher interviews revealed that the lack of CTPS habits at home, students who often forget, and improper handwashing techniques are the main factors that influence CTPS behavior at school. These findings indicate that although students' basic knowledge is quite good, habituation, mentoring, and environmental support are needed for consistent CTPS behavior.